Online estimation of the case fatality rate using a run‐off triangle data approach: An application to the Korean MERS outbreak in 2015. (5th March 2019) - Lee, Sungim; Lim, Johan
Abstract : This work is motivated by the recent Korean Middle East respiratory syndrome outbreak. We propose an easy online estimation procedure for the case fatality rate, ie, the proportion of deaths among the total cases during the course of an epidemic disease, which is an important indicator of the severity of a disease. The key step in our procedure is representing the data with the run‐off triangle, which simultaneously takes into account two time axes, namely, the calendar and disease‐duration times. We restructure the original data into run‐off triangle data, where the cells contain the numbers of cured patients, deceased patients, and patients still having the disease at a given combination of calendar and disease‐duration times. Based on the restructured run‐off triangle data, we propose an online estimator of the case fatality rate. We numerically show the advantages of the proposed estimator compared to the existing estimators in the literature. Finally, we apply our procedure to the 2015 Korean Middle East respiratory syndrome outbreak data.